An evolutionary complex systems perspective on urban health. (June 2021) - Liu, Jieling; Gatzweiler, Franz W.; Kumar, Manasi
Abstract: Deliberations about how to govern complex problems of urban health and wellbeing sustainably have often been implicitly biased by ideas such as being 'human-scale' or 'people-centered.' With increasing urban populations and increasing urban system interconnectivity, many cities have transformed into city regions or clusters, and the external effects of urban growth are carried mainly by the marginalized and the environment putting urban health increasingly at risk. Here we address the question of why human societies have not been better at collectively adapting to the challenges of urbanization and global environmental change? We build a theoretical framework of multi-level selection, complex systems evolution, and governance, following which we then present 'human-scale' and 'people-centered' ideas of urban development as expressions of two types of socio-political organization with different degrees of self-organization. We found several reasons for which the maladies of current urban development emerged and the seeming inability to resolve them. First, urban systems became increasingly interconnected and evolved into ultrasocial superorganisms, displaying preference to sustain themselves as a whole rather than their subordinates. Second, the difference in scaling effects between the biological and the social network contributed to the mismatch between rapid urban growth and slow adaptation. Furthermore, institutions of decreased variety reinforce themselves and become dominant, creating a positive feedback mechanism and promoting invasive and exploitative exponential growth, but they also reduce the creativity and resilience of urban systems. We also found that both the "human-scale" and the "people-centered" approaches acknowledge the exponential growth and decreasing variety in urban systems, and advocate for correcting the mismatches. To incorporate people's needs and values for long-term, truly sustainable urban health governance, we recommend combining the self-organizing, evolutionary feature of "human-scale" and the coordinative, political feature of "people-centeredness." Highlights: Urban systems evolved into interconnected, ultrasocial superorganisms, displaying tendencies to self-sustain. Biological and social networks differ in scaling effects, contributing to mismatch between rapid growth and slow adaptation. Institutions of decreased variety self-reinforce, creating positive feedback, promoting invasive and exploitative growth. Institutions of decreased variety also reduce the creativity and resilience of urban systems. Both human-scale and people-centered approaches acknowledge the decreasing variety and aim to resolve mismatches. Long-term, truly sustainable urban health governance must incorporate people's needs and values. We suggest combining the self-organizing and coordinative features of the two development approaches.